Parents' Choice Function for Wards' School Continuation in Rural India: A Case Study in West Bengal. (February 2016) - Thakur, Debdulal; Mukherjee, Shrabani
In this article, we present a choice function of a rural household relating to her/his ward's schooling. It makes an empirical evaluation on the basis of a simple theoretical framework using a primary data set surveyed from two backward districts of West Bengal. It explores the underlying causes of wards' discontinuation of school by examining the choice function of the parents using ordered probit analysis. The likelihood of dropout is higher at the primary level for low-income households and significantly depends on parents' attributes, which are mostly endogenous in an educational production function, and other exogenous difficulties in accessing school. It is also triggered by a lack of expectation about the future impact of education on a child's life. JEL Classification: C25, C80, D19, I21, I25